Moralidade como cooperação: evidências científicas - Sobroza Neto, João Batista (2022)
The present Dissertation consists of a review of the evidence for the thesis proposed by Curry et al. (2019) of a theory of morality-as-cooperation. We also set out to investigate whether allocation of resources to kin occupies a central and articulating role among the other universal positive valence moral behaviors listed by Curry et al. (2019), namely, helping your group, reciprocating, being brave, deferring to superiors, dividing disputed resources, and respecting prior possession. The central aim of the Dissertation is to show a successful case of clarifying philosophical positions on morality from an Evolutionary Cultural Anthropology perspective.